Agricultural households in times of crisis. The COVID-19 pandemic, livelihoods and land-use decisions - Kerstin Nolte; Kacana Sipangule; Niels Wendt (Journal of Land Use Science, 2022)
The COVID-19 pandemic has profound impacts on agricultural households. We discuss how these impacts might affect the underlying drivers of land-use decisions. First, we conceptually extend models of (smallholder) land-use decision-making to assess how the pandemic affects the underlying drivers of land-use decisions. We then examine effects on agricultural households' livelihoods, by drawing on high-frequency phone surveys from eight African countries and a literature review. We find that the COVID-19 pandemic affects these households' livelihoods substantially, reflected for instance, by reductions in various income sources. We further find that households' coping capabilities are weakened, meaning vulnerable households have difficulties to cope with the impacts of the pandemic. Agriculture is likely to become even more important in the years to come for households with very limited resources. Accordingly, we expect more labour-intensive uses of agricultural land. However, context matters and thus impacts on land-use are likely to be very variable.
Keywords: 330; Land-use change; agricultural household; COVID-19; Africa